2013
DOI: 10.4028/www.scientific.net/amr.814.99
|View full text |Cite
|
Sign up to set email alerts
|

Computer Simulation Paradigm Regarding the Structure and Mechanical Characteristics of Human Long Bones

Abstract: Given the complex form of the long bones, a quality method of geometrical modeling which provides a good result is that of the 3D modeling by reconstruction, using the principles of reverse engineering. One of the important problems that shall be taken into consideration while modeling is the one concerning the real structure of the bones. This aspect presents a lot of importance because from the point of view of the mechanical behavior, the bones are neither homogenate structures. In this paper a study of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Based on numerous research articles and studies, we concluded to a set of values which are of a healthy male subject, centralized in Table 1; data was harvested from [18][19][20]. This data will play a significant role in the further CAE modelling.…”
Section: The Real Structure Of the Bonementioning
confidence: 99%
See 1 more Smart Citation
“…Based on numerous research articles and studies, we concluded to a set of values which are of a healthy male subject, centralized in Table 1; data was harvested from [18][19][20]. This data will play a significant role in the further CAE modelling.…”
Section: The Real Structure Of the Bonementioning
confidence: 99%
“…The main fact that must be highlighted from of our previously made brief study is the high complexity of the bone structure. In order to accomplish the goal to model this structure, we applied the constructive-anatomical entity method [18,[21][22][23]. This specific method assumes dividing the main structure into several separate entities, which are then assembled as convenient for the 3D designer.…”
Section: The Real Structure Of the Bonementioning
confidence: 99%
“…Because the approach needs to be spatial, the requirement for a specialized device is obvious. An important starting point for doing this is the models and the inventions in the European and American literature [2,3,[12][13][14][15] which, however, appear to solve punctual problems, do not provide an overview of the requirement specific to the operation and neither a large degree of generality. Under the given conditions, the main objectives of conceiving and designing this device are the following:…”
Section: Designing and Modeling Of The Modular Device Used At The Higmentioning
confidence: 99%